The algorithm of numerical solution of the cauchy problem for tresca’s plasticity equations - Annin, Boris Dmitrievich; Alyokhin, Vladimir Vitalievich; Ostapenko, Vladimir Viktorovich (Computational Continuum Mechanics, 2008)
The problem of propagation of plastic zones in an unbounded medium from the boundary of a convex surface under normal pressure, tangential forces and given velocities is studied. When the medium is in the state of full plasticity, the system of quasistatic ideal plasticity Tresca equations describing the stress-strain state is hyperbolic. The difference scheme applied to hyperbolic systems of equations is proposed for the numerical solution of this system.